Gambaran Tingkat Pengetahuan dan Perilaku Responden pada Penggunaan Sunscreen di Klinik Kecantikan Wilayah Bekasi - Amirulah, Fajar; Yulianti, Yulianti; Yanti, Silfera Indra (Sinteza, 2024)
Sunlight contains ultraviolet rays that harm the skin, causing various kinds of skin disorders such as redness, premature aging, black spots, dryness, wrinkles, and skin cancer. Sunscreen is a skin care product that is useful for protecting the skin from the sun. This study aimed to determine the level of knowledge, attitudes, and behavior of female patients at the Beauty Clinic Region of Bekasi about the use of sunscreen. This study uses a descriptive method with a cross-sectional approach. The sample of 92 respondents at the Beauty Clinic Region of Bekasi was selected by purposive sampling by distributing questionnaires. The highest research results were obtained in the age group of 17-25 years as much as 38%, the Senior High School education group as much as 54,3%, the housewives occupation group as much as 35,9%, and private employees as much as 35,9%. The level of sufficient knowledge is 59,8%, sufficient attitude is 56,5% and sufficient behavior is 45,7%. Based on the results of this study, it can be concluded that the respondents at the Beauty Clinic Region of Bekasi have sufficient knowledge and behavior regarding the use of sunscreen.